Fine particulate matter, airway inflammation, stress response, non-specific immune function and buccal microbial diversity in young adults. (1st September 2022) - Lin, Zhijing; Chen, Ping; Yuan, Zhi; Yang, Liyan; Miao, Lin; Wang, Hua; Xu, Dexiang
Abstract: Fine particulate matter (PM2.5 ) has been associated with risk of oral and respiratory diseases. However, the biological mechanisms of adverse oral and respiratory health response to PM2.5 fluctuation have not been well characterized. This study aims to explore the relationships of PM2.5 with airway inflammation, salivary biomarkers and buccal mucosa microbiota. We performed a panel study among 40 college students involving 4 follow-ups from August to October 2021 in Hefei, Anhui Province, China. Health outcomes included fractional exhaled nitric oxide (FeNO), salivary biomarkers [C-reactive protein (CRP), cortisol, lysozyme and alpha-amylase] and buccal mucosa microbial diversity. Linear mixed-effect models were applied to explore the cumulative impacts of PM2.5 on health indicators. PM2.5 was positively correlated with FeNO, CRP, cortisol and alpha-amylase, while negatively with lysozyme. Per 10-μg/m 3 increase in PM2.5 was linked to maximum increments in FeNO of 10.71% (95%CI: 2.01%, 19.41%) at lag 0–24 h, in CRP of 7.10% (95%CI: 5.39%, 8.81%) at lag 0–24 h, in cortisol of 1.25% (95%CI: 0.44%, 2.07%) at lag 0–48 h, and in alpha-amylase of 2.12% (95%CI: 0.53%, 3.71%) at lag 0–24 h, while associated with maximum decrement in lysozyme of 0.53% (95%CI: 0.12%, 0.95%) at lag 0–72 h. Increased PM2.5 was linked to reduction in the richness and evenness of buccal microbe and o_Bacillales and o_Bacteroidales were identified as differential microbes after PM2.5 inhalation. Bio-information analysis indicated that immunity system pathway was the most important enriched abundant process altered by PM2.5 exposure. In summary, short-term PM2.5 exposure may impair oral and respiratory health by inducing inflammatory and stress responses, weakening immune function and altering buccal mucosa microbial diversity. Graphical abstract: Image 1 Highlights: We estimated the acute effects of PM2.5 on adults' oral and respiratory health. Short-term exposure to PM2.5 may increase airway inflammation and stress levels. Short-term exposure to PM2.5 may weaken non-specific immune function. Bio-information analysis revealed PM2.5 most obviously influenced immunity system. Short-term exposure to PM2.5 may alter buccal mucosa microbial diversity.